การจัดการเรียนรู้แบบ AGGIE Model - ไชยสถาน, เอกรัก (วารสาร มมร ยศสุนทรปริทรรศน์; Vol 2 No 3 (2025): วารสาร มมร ยศสุนทรปริทรรศน์ ปีที่ 2 ฉบับที่ 3 : กันยายน - ธันวาคม 2568, 2025)
This article aims to develop and present the AGGIE Model of Learning Management, an approach that integrates the core principles of Active Learning and Learner-Centered instruction. The model consists of five key steps: 1) Awareness, which stimulates students to recognize the importance and goals of learning; 2) Goals, which encourages students to set clear and challenging objectives for themselves; 3) Guidance, which redefines the teacher's role from a knowledge transmitter to a facilitator and mentor; 4) Implementation, which provides opportunities for students to engage in hands-on activities and construct their own knowledge; and 5) Evaluation, which promotes continuous self-reflection and assessment of learning outcomes.           Implementing the AGGIE Model helps foster sustainable learning skills in students, enabling them to adapt and become effective lifelong learners in the digital age. This approach is highly relevant for developing the essential competencies needed for the 21st century.